Evaluasi dan Perencanaan Pengembangan Sistem Jaringan Listrik Kampus Politeknik Negeri Ambon - Pieter S. Tatipikalawan; Wijono Wijono; Rini Nur Hasanah (Fakultas Teknik, Universitas Brawijaya, 2015)
This paper discusses the evaluation of the electrical system at the Polytechnic of Ambon. Problems arise when this is a very poor network conditions that supply to each building. In some buildings often have on limiting current trip. This occurs because the addition of the load from time to time but was not followed by changes in installations that meet the standards. Evaluation is done with the help softwaare Docwin and Matlab. These include standardization of electrical networks, voltage profile, the data load and network installation. Evaluation results show that the current network conditions is not feasible and over load. Improvements to the current network is also proposed in this paper, because the proposal to be considered in the planning of the electrical network repair Polytechnic Campus Ambon in the future.Index Terms — Evaluation, planning, electric network System, Polytecnic of Ambon, DocWin and Matlap.